What Factors Contribute to Speech Delay in Early Childhood?: A Case Study of Kindergarten Students in Central Kalimantan - Fariza, Yulia; Hartanti, Sofia; Wulan, Sri; Vanalestari, Adisty (Electronic Journal of Education, Social Economics and Technology, 2025)
Early childhood is a critical period for language development because it supports communication, social interaction, and later academic achievement. However, some children experience speech delay that limits their participation in learning activities. This study aimed to examine factors associated with speech delay in early childhood and to analyze the challenges faced by teachers and the strategies used in classroom settings. This research employed a qualitative case study design involving five children identified with speech delay in an early childhood education context. Data were collected through semi-structured interviews with teachers and parents and analyzed using thematic analysis. The findings indicate that speech delay is influenced by several factors, including limited verbal stimulation at home, early exposure to digital media, limited social engagement, emotional and behavioral aspects of speech, and speech articulation and production difficulties. Teachers reported challenges such as limited verbal output, reliance on non-verbal communication, selective peer interaction, reduced participation in group learning activities, and limited parental awareness of children’s speech difficulties. To address these challenges, teachers implemented individualized verbal stimulation, play-based language activities, structured instructional support, peer-mediated interaction, and parent–teacher collaboration. The study highlights the importance of collaboration among teachers, parents, and relevant professionals in supporting children’s speech and language development.